Pendampingan Baca Tulis Al-Qur’an Dengan Menggunakan Metode Ummi Dimadrasah Diniyah Takmiliyah Awaliyah Babussalam Desa Kotodua - Muhammad Habil; Martin Kustati; Rezki Amelia (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2024)
This assistance aims to determine children's ability to read and write the Koran in the village of Kotodua, Sungai Full City, Jambi Province. Mentoring is carried out through face-to-face learning for children. This mentoring uses the ummi method and evaluation practice. Evaluation of the mentoring results is carried out in writing and orally. Data collected through interview techniques, observation and documentation. The results of this service show that assisting children in reading and writing the Al-Qur'an is through the application of the ummi method, namely: (a) the child is able to recite and recognize the hijaiiyah letters in the Al-Qur'an (b) the child is able to read and write Al-Qur'an. Qur'an (c) the child is able to follow the reading taught by the teacher and (d) the child is able to repeat the reading of the Qur'an that has been taught previously. The results given were considered good, making the participants' writing and reading abilities improve and their knowledge about religion increased. Considering the large benefits provided in this service program